VIDEO INTERAKTIF ANIMATOON BERBASIS PROFIL PELAJAR PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA - Ni Putu Sri Wahyu Dewi, Dewi; I Komang Sudarma; Ni Wayan Eka Widiastini (Jurnal Media dan Teknologi Pendidikan, 2025)
Pancasila Education in elementary schools is a learning process designed to instill Pancasila values from an early age through knowledge mastery, attitude habituation, and the application of behaviors that reflect morals, ethics, and national character. However, student learning outcomes in this subject remain relatively low, partly due to the lack of engaging media suited to elementary school characteristics. As an essential foundation, Pancasila Education plays a key role in shaping students’ character, especially in strengthening the Pancasila Student Profile. This study aimed to develop an interactive video learning media called Animatoon based on the Pancasila Student Profile to improve fourth-grade students’ learning outcomes. The research used the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. Data were collected through interviews, questionnaires, and tests, and analyzed using both quantitative descriptive and qualitative descriptive methods. The results indicated that: (1) the Animatoon interactive video is valid and practical based on expert evaluations and student trials, and (2) the media is effective in enhancing learning outcomes, supported by the Paired Sample T-Test result with a significance value of 0.000 (< 0.05). These findings demonstrate that the Animatoon video is not only feasible but also effective for use in elementary school learning, particularly in Pancasila Education. In conclusion, the development of this interactive video contributes to improving student learning outcomes while supporting the strengthening of the Pancasila Student Profile. Moreover, it has implications for enhancing both the quality of learning and overall educational outcomes.